Cathepsin S: molecular mechanisms in inflammatory and immunological processes - Gao, Huan; Zhang, Zirui; Deng, Jiayu; Song, Yanqing (Frontiers in Immunology, 2025)
Cathepsin S (CTSS), a lysosomal cysteine protease predominantly expressed in immune cells, governs inflammatory and immunological cascades through proteolytic activity. Beyond maintaining lysosomal proteostasis through protein degradation, CTSS executes dual immunomodulatory functions: intracellularly processing antigen-presenting molecules and modulating inflammatory signaling cascades; extracellularly activating protease-activated receptors (PARs) and remodeling the extracellular matrix (ECM). Its dysregulation drives pathology in autoimmune disorders, chronic inflammation, and neoplasia, establishing CTSS as a multifaceted therapeutic target. This review comprehensively explores the contributions of CTSS signaling in immune-mediated inflammatory diseases, critically evaluates its therapeutic potential, highlighting its significance in the development of innovative treatment strategies.